2013
DOI: 10.1007/s12070-013-0648-4
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume: Is It a Predictive Parameter in The Diagnosis of Sudden Sensorineural Hearing Loss?

Abstract: The mean platelet volume (MPV) is associated with increased platelet reactivity and increased atherothrombosis. High MPV values are a risk factor for thrombotic vascular diseases. Our aim was to investigate whether a relationship exists between sudden sensorineural hearing loss (SSHL) and a high MPV value. The records of 46 patients who were admitted to the ENT (ear nose throat) ward for SSHL and received medical treatment and 46 patients in a control group were retrospectively screened. The correlation among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 32 publications
2
40
1
1
Order By: Relevance
“…Ulu et al [23] reported significantly higher MPV levels in ISSNHL patients and suggested that increased MPV values indicate the possible causes of ischemia or atherosclerosis in ISSNHL patients. However, Karli et al [24] have reported no significant difference between MPV levels of ISSN-HL patients and controls.…”
Section: Discussionmentioning
confidence: 93%
“…Ulu et al [23] reported significantly higher MPV levels in ISSNHL patients and suggested that increased MPV values indicate the possible causes of ischemia or atherosclerosis in ISSNHL patients. However, Karli et al [24] have reported no significant difference between MPV levels of ISSN-HL patients and controls.…”
Section: Discussionmentioning
confidence: 93%
“…Poorey et al [31] reported an increased level of MPV due to chronic nasal obstruction in patients with deviated nasal septum. Karli et al [6] stated that MPV is not a predictive parameter in the diagnosis of sudden sensorineural hearing loss. Ozbay et al [22] found no significant difference in terms of MPV levels between patients with severe tinnitus and control subjects.…”
Section: Ent Updatesmentioning
confidence: 99%
“…[40][41][42] Mean platelet volume (MPV) is a blood marker related to function and activation of platelets. 43 A study on patients with stroke reported that NLR increase and CRP (C reactive protein) which is an inflammation marker are significantly correlated. 44 The study by Gokhan et al showed NLR scores increase significantly in ischemic and hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%